2020
DOI: 10.1111/gcb.15206
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature increases the accumulation of microbial necromass nitrogen in soil via increasing microbial turnover

Abstract: Microbial-derived nitrogen (N) is now recognized as an important source of soil organic N. However, the mechanisms that govern the production of microbial necromass N, its turnover, and stabilization in soil remain poorly understood. To assess the effects of elevated temperature on bacterial and fungal necromass N production, turnover, and stabilization, we incubated 15 N-labeled bacterial and fungal necromass under optimum moisture conditions at 10°C, 15°C, and 25°C. We developed a new 15 N tracing model to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 75 publications
4
42
0
Order By: Relevance
“…Therefore, despite overall C limitation, the fast-growing taxa prevalent at 35°C may have benefitted from a high N acquisition potential, enabling rapid growth fueled from necromass N. In line with this view, fast-growing microorganisms have been proposed to have a relatively high N demand (Fierer et al, 2007;. Wang et al (2020) (2020), mineralization of necromass N may also explain the strong increase in NH 4 + concentrations at 35°C in this study. As microbial biomass is rich in N (Xu et al, 2013), and the fast-growing high-temperature community is assumed to have a high energy demand, recycling of microbial necromass is expected to exacerbate the C limitation in the studied soil, which is supported by the decreased DOC:DON ratio at 35°C compared with 4°C as well as by the strong increase in inorganic N at 35°C (Table 1).…”
Section: Changes In the Microbial N-cycling Potential And Linkages supporting
confidence: 67%
“…Therefore, despite overall C limitation, the fast-growing taxa prevalent at 35°C may have benefitted from a high N acquisition potential, enabling rapid growth fueled from necromass N. In line with this view, fast-growing microorganisms have been proposed to have a relatively high N demand (Fierer et al, 2007;. Wang et al (2020) (2020), mineralization of necromass N may also explain the strong increase in NH 4 + concentrations at 35°C in this study. As microbial biomass is rich in N (Xu et al, 2013), and the fast-growing high-temperature community is assumed to have a high energy demand, recycling of microbial necromass is expected to exacerbate the C limitation in the studied soil, which is supported by the decreased DOC:DON ratio at 35°C compared with 4°C as well as by the strong increase in inorganic N at 35°C (Table 1).…”
Section: Changes In the Microbial N-cycling Potential And Linkages supporting
confidence: 67%
“…This might explain the positive relationship between clay content and soil AS content (Table S5). However, very few studies have quantified the decomposition rate of microbial necromass and its temperature sensitivity (Wang, Wang, Cotrufo, et al, 2020; Wang, Wang, Pei, et al, 2020). Future research is needed to study this parameter and its response to environmental factors in order to better incorporate the microbial necromass pool in ESMs.…”
Section: Discussionmentioning
confidence: 99%
“…Results from models indicated that the contribution of microbially derived necromass C to the formation of SOC could be from 10% to 80% (Fan et al, 2021; Liang et al, 2019; Simpson et al, 2007). Moreover, this C has been found to have different structural components and different decomposition patterns from plant‐derived C (Simpson et al, 2007; Wang, Wang, Cotrufo, et al, 2020; Wang, Wang, Pei, et al, 2020). Therefore, the high contribution of microbial necromass to SOC could be due to their relative slow decomposition rate or the higher chance of mineral protection from decomposition by microorganisms or both (Hagerty et al, 2014; Li et al, 2018; Miltner et al, 2012; Wang, Wang, Cotrufo, et al, 2020; Wang, Wang, Pei, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations